2022
DOI: 10.1186/s12866-022-02651-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus YRB2 from Thymelaea hirsuta (L.) Endl., a non-aflatoxigenic endophyte with ability to overexpress defense-related genes against Fusarium root rot of maize

Abstract: Fusarium root rot, caused by Fusarium solani (Mart.) Sacc., represents one of the most damaging diseases of maize affecting plant growth and yield. In this study, the antagonistic potential of a non-aflatoxigenic endophytic Aspergillus flavus YRB2, isolated from Thymelaea hirsuta (L.) Endl., was tested against F. solani in vitro. In addition, its biocontrol activity against Fusarium root rot of maize was evaluated under greenhouse conditions. Its impacts on plant molecular, pathological, physiological, and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Endophytic microorganisms are promising resources of biofertilizers, natural antimicrobial compounds, and growth promotors, which can be used as green advances to reduce the use of agrochemicals 71 , 72 . Other researchers have confirmed similar findings, demonstrating the beneficial effects of endophytic microorganisms where it is important for developing feasible replacements for chemicals like fungicides and insecticides, as well as the recurrent problems of their uncritical use and could apply the endophytes for plant growth promotion and prevention of fungal infections 73 , 74 . The plant growth-promoting abilities of endophytic fungus, and recent advances in our knowledge of some of the mechanisms, imply that this interesting source warrants additional exploration for possible future use in agriculture.…”
Section: Discussionmentioning
confidence: 57%
“…Endophytic microorganisms are promising resources of biofertilizers, natural antimicrobial compounds, and growth promotors, which can be used as green advances to reduce the use of agrochemicals 71 , 72 . Other researchers have confirmed similar findings, demonstrating the beneficial effects of endophytic microorganisms where it is important for developing feasible replacements for chemicals like fungicides and insecticides, as well as the recurrent problems of their uncritical use and could apply the endophytes for plant growth promotion and prevention of fungal infections 73 , 74 . The plant growth-promoting abilities of endophytic fungus, and recent advances in our knowledge of some of the mechanisms, imply that this interesting source warrants additional exploration for possible future use in agriculture.…”
Section: Discussionmentioning
confidence: 57%
“…The JERF3 gene was particularly expressed in response to treatment of eggplants with N. circulans YRNF1 and AMF. The gene JERF3 controls several plant defense genes (Rashad et al, 2022b). PAL1 regulates the main step in the polyphenolic biosynthetic pathway, through conversation of phenylalanine to t-cinnamic acid (Mouradov and Spangenberg, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Triggering immunity-related genes in plants is an important mode of action of biocontrol agents. Jasmonic acid and ethylene-response factor 3 gene (JERF3), the responsive gene that manages several defence-response genes through the jasmonate/ethylene signalling path-way, is elicited by abiotic and biotic plant stresses (Rashad et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…39 The VBs of WT and DPA were damaged and collapsed due to fungal growth, similarly, the roots and stems of corn plants were infected by a pathogenic strain of F. verticillioides. 40 In addition, the sclerenchyma cells provide mechanical support to VBs through thickening primary cell walls, which further acts as a mechanical barrier against fungal invasion. The present study revealed higher numbers of sclerenchyma cells in WT as compared to DPA during Fusarium infection.…”
Section: Discussionmentioning
confidence: 99%